2020
DOI: 10.3390/ijerph17207539
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Assessments of Risk Factors for Cardiovascular Diseases in Labors: An Application of Metabolic Syndrome Scoring Index

Abstract: Unlike a traditional diagnosis of metabolic syndrome (MS), a numerical MS index can present individual fluctuations of health status over time. This study aimed to explore its value in the application of occupational health. Using a database of physiological and biochemical tests and questionnaires, data were collected from 7232 participants aged 20 to 64 years who received occupational health screenings at a health screening institution in 2018. Using confirmatory factor analysis, five components of MS were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…(6) confirmed that the long-term exposure to noise in the work environment increased the chance of suffering from MS in the Chinese professional population (6). At the same time, some related studies confirmed the relationship of MS with the type of work in different occupational groups (7)(8)(9). Therefore, performing early MS screening for the occupational population is of great significance.…”
Section: Introductionmentioning
confidence: 65%
“…(6) confirmed that the long-term exposure to noise in the work environment increased the chance of suffering from MS in the Chinese professional population (6). At the same time, some related studies confirmed the relationship of MS with the type of work in different occupational groups (7)(8)(9). Therefore, performing early MS screening for the occupational population is of great significance.…”
Section: Introductionmentioning
confidence: 65%
“…This may be because senior workers or those with a higher level of education may be more likely to be assigned to managerial roles with greater responsibilities, especially during emergencies. A Taiwanese study found that managers have higher risks of MS and CVDs [ 40 ]. The authors also suggested that these managers might have been promoted due to their own professional expertise, so might endure more work-related stress and health risks.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al confirmed that the long-term exposure to noise in the work environment increased the chance of suffering from MS in the Chinese professional population [6]. At the same time, some related studies confirmed the relationship of MS with the type of work in different occupational groups [7][8][9]. Therefore, performing early MS screening for the occupational population is of great significance.…”
Section: Introductionmentioning
confidence: 98%